KARSINOMA KELENJAR SEBASEA DI PALPEBRA SUPERIOR MATA KIRI: LAPORAN KASUS - Raudatul Janah (Jurnal Kedokteran Syiah Kuala, 2021)
Abstrac: Sebaceous gland carcinoma is a rare and fast-growing, potentially lethal skin malignant tumor originating from the adnexal epithelium of the sebaceous glands. This carcinoma is more common in the superior palpebral than the inferior palpebral in a ratio of 3:1 and is more common in the elderly with a predilection for women. Because it is clinically similar to a chalazion or a chronic inflammatory condition that can cause delays in diagnosis. Because of this rarity, we report a case of sebaceous gland carcinoma of the superior palpebral left eye in a 67-year-old man. Keyword. Sebaseous gland carcinoma, superior palpebral, ocular sinistra